2003
DOI: 10.1097/01.tp.0000087833.48999.3d
|View full text |Cite
|
Sign up to set email alerts
|

Live related renal transplantation: psychological, social, and cultural issues

Abstract: Cadaveric donation rates have remained static, whereas transplant waiting lists continue to rise as demand for renal transplants far exceeds supply. One solution to bridge the supply and demand gap is to increase live donation. If live donation is to increase, it is important to offer evidence-based psychologic and social support to ensure that transplant clinical success is not at the cost of psychologic and social harm. This article reports the findings of two substantive qualitative studies, both examining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
87
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 6 publications
11
87
1
Order By: Relevance
“…In a study of living-related kidney transplantation, Reimer et al (19) observed that the donation led to family conflict in 5 cases (10.6%) and divorce in 3 cases (6.4%). A United Kingdom study (20) of renal transplantation again examined the psychologic and social-cultural perspectives of live donation and determined that donation may lead to anxiety regarding marriage and marital failure, and affect the other members of the family. Rodrigue et al (21) examined the parenting stress, coping strategies and family functioning among 27 mothers of children undergoing bone marrow, liver, kidney, and heart transplantation at the pretransplant stage and at 1-and 6-month posttransplant stages.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of living-related kidney transplantation, Reimer et al (19) observed that the donation led to family conflict in 5 cases (10.6%) and divorce in 3 cases (6.4%). A United Kingdom study (20) of renal transplantation again examined the psychologic and social-cultural perspectives of live donation and determined that donation may lead to anxiety regarding marriage and marital failure, and affect the other members of the family. Rodrigue et al (21) examined the parenting stress, coping strategies and family functioning among 27 mothers of children undergoing bone marrow, liver, kidney, and heart transplantation at the pretransplant stage and at 1-and 6-month posttransplant stages.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Many patients are also unaware that living donors report positive benefi ts from donating, including getting to help a loved one and having increased selfworth. 22,23 Multiple randomized controlled trials have shown that improved education about deceased and living donation can signifi cantly increase patients' knowledge and informed transplant decision-making. [24][25][26][27][28] However, with dialysis patients varying in their level of readiness regarding pursuing deceased or living-donor transplant, transplant education must be tailored by a patient's level of transplant readiness to support each individual in making an informed transplant choice.…”
mentioning
confidence: 99%
“…Jacobs et al (1998) have observed also that donors were more likely to feel pressured to donate if the recipient was a sibling or offspring and the initial approach for donation came from family members. This external pressure may be felt when family members or medical professionals make a direct request for living donation to the potential donor and there is a psychological cost to the potential donor if they refuse (e.g., Franklin & Crombie, 2003;Russell & Jacob, 1993;Schroder, McDonald, Etringer, & Snyders, 2008). Potential donors may be motivated also to donate while living to a relative or partner because of feelings of responsibility, duty, or internal pressure to do the morally correct thing for their family member (Hilhorst, Kranenburg, & Busschbach, 2007;Russell & Jacob, 1993).…”
mentioning
confidence: 99%